Pelaksanaan Penilaian Daring di Masa Pandemi Covid-19 - Aditya Erwin Herlambang; Hanita Yulia (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2022)
Cognitive, affective, and psychomotor assessments are significant in the learning process and should be done effectively, even in online learning. Therefore, this study aims to describe the implementation of online assessments in productive subjects in SMKN 3 Salatiga. This is a descriptive qualitative research using snowball sampling as a sampling technique. In-depth interviews to 10 teachers and qualitative observation were conducted to obtain the data. Data were analyzed using Miles and Huberman model which consisted of three steps (data reduction, data display, and conclusion drawing). The findings were all teachers conducted the online assessments in cognitive and affective domain. However, not all teachers conducted online psychomotor assessment. Internet access and technology devices became the main problems for online assessments implementation. The error system or application, lack of time, students’ discipline and activeness also became the challenge in online assessment. Some solutions such as rescheduling, changing the application, and communicating with parents were done. Offline assessments using health protocol of COVID-19 became the last choice to do.